Good practice in der institutionellen Kommunikation Von der Deskription zur Bewertung in der Angewandten Gesprächsforschung - Bendel Larcher, Sylvia; Pick, Ina (Sprache im Kontext / Language in Context, 2023)
How can we identify successful linguistic action in recordings of institutional conversations? The theoretical-methodological contributions discuss what the basis for evaluation is, how it can be collected empirically, and how good practice can be identified in the discussion. The empirically oriented contributions analytically elaborate concrete forms of good practice for different institutional settings.